Experimentally Assess How Self-healing Agents, Specifically Bacterial Additives, Influence the Mechanical Properties of Concrete Including Compressive, Tensile, and Flexural Strengths (International Journal of Scientific Research in Science and Technology, 2026)
This work explores the use of bacteria, Bacillus subtilis, to improve concrete’s tensile, compressive, and flexural strength. Results show that bacteria significantly enhance these properties, with increases of up to 6.8%, 28.06%, and 2.90%, respectively. Bacteria’s ability to produce calcite and other minerals creates a denser, more cohesive concrete microstructure. X-ray diffraction (XRD) analyses confirm the formation of these minerals, contributing to the strength enhancement. This innovative approach offers a sustainable and environmentally friendly method for improving concrete’s mechanical properties. Utilizing bacteria and calcium lactate during the mixing phase to boost strength is an example of how concrete technology has improved. The percentages of materials used in the mixing procedure for the study were 0%, 5%, 7%, 9%, and 0%, 10%, 8%, and 6%, respectively. The creation of calcium carbonate crystals, which close pores and cracks, is the result of adding bacteria and calcium lactate powder in an experiment that shows this bacterial concrete increases compressive strength. In order to convert the precursor component into the best filler substance, bacteria and calcium lactate, Bacillus subtilis was employed for extended periods of time as a catalyst.